As antinomias nas normas jurídicas da Primeira República: do cerceamento da prática do espiritismo e à concessão da liberdade religiosa através de habeas corpus - Gomes, Adriana (Sacrilegens, 2016)
In 1890 the Brazilian Penal Code criminalized spiritism, especially its practices related to the "art of healing". Spiritist citizens were vulnerable to punishment in articles 156, 157 and 158 of the criminal legislation regarding crimes against public health. In addition, with the creation of the Sanitary Regulation in Rio de Janeiro (1904), the criminalization of spiritualism gained incitement and there was a greater impetus to reprimand the spiritists who worked in the area of alternative medicine. The practice of spiritism was understood as a challenge to public order. In this historical context, the "clerk" Francisco Nogueira da Silva requested the court to grant a preventive habeas corpus under the allegation of curtailing the right to religious freedom and conscience protected by the 1891 Constitution.